Altered balance between self-reactive T helper (Th)17 cells and Th10 cells and between full-length forkhead box protein 3 (FoxP3) and FoxP3 splice variants in Hashimoto's thyroiditis. (10th March 2015) - Kristensen, B; Hegedüs, L; Madsen, H O; Smith, T J; Nielsen, C H
Summary: T helper type 17 (Th17) cells play a pathogenic role in autoimmune disease, while interleukin (IL)-10-producing Th10 cells serve a protective role. The balance between the two subsets is regulated by the local cytokine milieu and by the relative expression of intact forkhead box protein 3 (FoxP3) compared to FoxP3Δ2, missing exon 2. Th17 and Th10 cell differentiation has usually been studied using polyclonal stimuli, and little is known about the ability of physiologically relevant self-antigens to induce Th17 or Th10 cell differentiation in autoimmune thyroid disease. We subjected mononuclear cells from healthy donors and patients with Hashimoto's thyroiditis (HT) or Graves' disease (GD) to polyclonal stimulation, or stimulation with human thyroglobulin (TG), human thyroid peroxidase (TPO), or Esherichia coli lipopolysaccharide (LPS). TPO and LPS induced increased differentiation of naive CD4 + CD45RA + CD45R0 – T cells from HT patients into Th17 cells. Th10 cell proportions were decreased in HT after polyclonal stimulation, but were comparable to those of healthy donors after antigen-specific stimulation. Taken together, our data show that an increased Th17 : Th10 ratio was found in HT patients after stimulation with thyroid-specific self-antigens. We also observed an elevated baseline production of IL-6 and transforming growth factor (TGF)-β1 and of mRNA encoding FoxP3Δ2 rather than intact FoxP3. This may contribute to the skewing towards Th17 cell responses in HT.